Application of a small-scale model test in distinguishing of water inrush in the Wufeng Tunnel - Xiaochuan Xu; Guangli Xu; Gaowei Lin; Yiyuan Li; Yun Ma (地质科技通报, 2023)
Objective Water inrush in karst tunnel has a great influence on tunnel safety. Methods Taking the Wufeng Tunnel of Yilai Expressway as the research object, the risk of water inrush in the tunnel was identified though field hydrogeological investigation, borehole water level and indoor rainfall monitoring, numerical simulation and small-scale model tests. Results The test results show that the risk of water inrush in the tunnel is mainly affected by the relative spatial position between the karst pipeline and tunnel, including the water pressure of the pipeline. The influence of seepage on the tunnel can be effectively reduced by increasing the thickness of the overlying soil when the test water pressure is 0.2 MPa. But with the increase in water pressure, the seepage of pipeline water is not only vertical seepage but also includes horizontal seepage. The intermittent cracks in the waterproof layer expand, which finally results in water inrush damage in the tunnel. The numerical simulation results show that the maximum shear force of the Wufeng Tunnel is at the arc and shoulder, which may easily form tensile shear failure along this part under groundwater seepage. The finding is consistent with the test results of the small-scale model. The water inrush in the tunnel is the coupling effect of the shear force and seepage field. Conclusion The primary factor of water inrush in the tunnel is water pressure and is closely related to the thickness of water barrier rock.